Impact of hypotension and global hypoperfusion in postoperative delirium: a pilot study in older adults undergoing open colon surgery - Eduardo Tobar; Mario A. Abedrapo; Jaime A. Godoy; Jose L. Llanos; Mauricio J. Díaz; Rodrigo Azolas; Gunther R. Bocic; Jaime A. Escobar; Rodrigo A. Cornejo; Carlos M. Romero (Revista Brasileira de Anestesiologia)
Abstract Background: Post-operative delirium is a serious complication in patients undergoing major abdominal surgery. It remains unclear whether peri-operative hemodynamic and perfusion variables affect the risk for postoperative delirium. The objective of this pilot study was to evaluate the association between perfusion and hemodynamics peri-operative with the appearance of post-operative delirium. Methods: Prospective cohort study of adults 60 years or older undergoing elective open colon surgery. Multimodal hemodynamic and perfusion variables were monitored, including central venous oxygenation (ScvO2), lactate levels, and non-invasive cerebral oxygenation (rSO2), according to a standard anesthesia protocol. Fisher's exact test or Student's t-test were used to compare patients who developed post-operative delirium with those who did not (p < 0.05). Results: We studied 28 patients, age 73 ± 7 years, 60.7% female. Two patients developed post-operative delirium (7.1%). These two patients had fewer years of education than those without delirium (p = 0.031). None of the peri-operative blood pressure variables were associated with incidence of post-operative delirium. In terms of perfusion parameters, postoperative ScvO2 was lower in the delirium than the non-delirium group, without reaching statistical significance (65 ± 10% vs. 74 ± 5%; p = 0.08), but the delta-ScvO2 (the difference between means post-operative and intra-operative) was associated with post-operative delirium (p = 0.043). Post-operative lactate and rSO2 variables were not associated with delirium. Conclusions: Our pilot study suggests an association between delta ScvO2 and post-operative delirium, and a tendency to lower post-operative ScvO2 in patients who developed delirium. Further studies are necessary to elucidate this association.